Uncertainty (Gharar) in the Indonesian Islamic Higher Education System - Halim Faqihuddin Annasr; Ibdalsyah; Qurroh Ayyuniyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Many financial transactions in Islamic higher education institutions in Indonesia have not exactly suitable for Sharia principles, especially in areas such as academic fees and financial contributions. One of the main key issues in these transactions is the presence of gharar, which refers to uncertainty or ambiguity that may disadvantage one of the parties involved. The lack of transparency in contracts and payment mechanisms is a major factor contributing to gharar. In Islamic law, transactions containing gharar are prohibited as they can lead to injustice in contractual agreements. This study aims to identify the presence of gharar in financial transactions within Islamic higher education institutions in Indonesia and to analyze its implications for the validity of contracts and compliance with Sharia principles. A qualitative descriptive method was employed, incorporating three primary approaches: in-depth interviews with key policymakers in Islamic higher education institutions, document analysis of fiqh sources related to Sharia-compliant transactions, and direct observation of financial transaction practices within the institutions. The findings indicate that certain financial transactions in Islamic educational institutions contain elements of gharar, particularly in terms of fee transparency and contractual ambiguity. A lack of clarity in payment mechanisms can lead to misunderstandings between institutions and students, potentially resulting in financial disputes. However, this study also finds that gharar does not automatically invalidate contracts, as long as it remains within an acceptable threshold according to fiqh muamalah, especially when gharar is not a dominant factor in the transaction. These findings highlight the need for clearer regulations in the financial systems of Islamic higher education institutions, including standardized contractual frameworks and greater transparency in fee structures, to minimize ambiguity in transactions and enhance adherence to Sharia principles. Therefore, collaboration among educational foundations, administrative staff, students, and parents is essential to ensure that all transactions are conducted with full transparency and free from gharar, as prohibited in Islamic teachings.